Development and physiology of the heart - Bodmer, Rolf (Henry Stewart Talks, 2008)
Genetic basis of heart development, function and aging, Genetic model (Drosophila) for heart research, Drosophila model for congenital heart disease, Drosophila model for arrhythmias and cardiomyopathies, Drosophila model for age-dependent heart disease
Reviewed at 2018/05/31